The Need for Christian-Muslim Dialogue in Nigeria - Nzeyo Gabriel Eteng; Gbagu Aaron Sekegh (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2021)
The paper, titled "The Need for Christian-Muslim Dialogue in Nigeria," is motivated by the religious crises that exist between Christians and Muslims, resulting in the loss of lives and property worth billions of naira for decades. Most recently, the northern parts of the country have experienced so many crises between Christians and Muslims. Therefore, there is a call for dialogue between these religions. The method adopted to gather and analyze the data in this research is the quantitative method, which is basically works written by scholars found in books, journals, and internet sources, and the researchers’ experiences. The study, which is anchored on the Christian-Muslim dialogue in Nigeria, discovered the associated challenges to the peaceful co-existence of Christians. The paper discovered that Christian-Muslim dialogue will lead to peaceful co-existence, interreligious and social harmony, interfaith unity, and religious unification, etc. One of the recommendations made in this paper is that Christians and Muslims should not ignore Biblical and Quranic teachings that form the ethics of their religions. Secondly, Christian-Muslim dialogue is the bane of understanding and peaceful co-existence in Nigerian society.